تأثير استخدام طريقة الباقيان الضيفان على قدرة التلاميذ على استيعاب المفردات العربية: بحث تجريبي في الفصل الاوّل المتوسّط بمعهد الإمام الذّهبي كمبار، رياو - Berampu, Restu Permana (CV Global Research Publication, 2024)
The research method used is quantitative research in the form of an experiment, utilizing statistical calculation methods. The purpose of this study is to determine the value of understanding Arabic vocabulary using the Two Stay Two Stray method and not using it in the seventh grade at Ma'had Imam Adz-Dzahabi Kampar. Additionally, it aims to understand the influence of the Two Stay Two Stray method on students' ability to understand Arabic vocabulary in the seventh grade at Ma'had Imam Adz-Dzahabi Kampar. The results obtained from this study show that the average score of students in understanding Arabic vocabulary after the implementation of the Two Stay Two Stray method is 84.79, whereas the average score before the implementation of this method was 74.12. The study also indicates that this method affects students' ability to understand Arabic vocabulary based on the t-test calculation results of 2.06 < 8.76 > 2.80. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In conclusion, the use of the Two Stay Two Stray method can influence students' vocabulary. There is a difference in vocabulary learning between using the Two Stay Two Stray method and not using this method.